Strategi Tata Kelola Kebijakan Penanganan Anak Rentan dan Tidak Sekolah di Kota Pekalongan - Agus Wahyudi; Mustofa Anshori Lidinillah; Hendro Muhaimin; Rona Utami (JURNAL LITBANG KOTA PEKALONGAN, 2025)
Education is a fundamental right guaranteed by the constitution for every citizen. However, in Pekalongan City, a significant challenge persists: many children lack access to quality education due to economic, social, and other constraints. The issues of Out-of-School Children (OSC) and those vulnerable to dropping out remain pressing problems that demand serious attention from the government and stakeholders. This study employs a qualitative approach with an ethnographic method to explore these issues in depth. The ethnographic approach facilitates a thorough examination of local innovations addressing OSC in Pekalongan City, including identifying the roles of key stakeholders. The research aims to uncover best practices and assess the sustainability of current educational initiatives. Focus group discussions (FGDs) are conducted with stakeholders such as the Pekalongan City Development Planning Agency (Bappeda) for policy alignment and the Pekalongan City Education Office for technical implementation. This study identifies the strategies and policies already implemented, emphasizing the importance of cross-sector collaboration and active participation from stakeholders to build an inclusive and equitable education system. The findings of this research highlight the necessity of a collective commitment from the government, educational institutions, communities, and individuals to address these challenges. This shared effort is essential to achieving the vision of inclusive and high-quality education in Pekalongan City.